TEKNIK ESTIMASI DAN KOMPENSASI GERAK PADA VIDEO CODING FGS (Fine Granularity Scalability) - Agus Purwadi; Afrizal Yuhanef; Lince Markis (Elektron : Jurnal Ilmiah, 2013)
Motion estimation is a process to determine the movement of an object on video sequential. The movement of objects is known as motion vector. A motion vector indicates a shift point between the current frame with the reference frame. Of motion vector is obtained, it would seem that the movement of the dots between the observed frame. In this study using the algorithm block maching SAD (Sum of Absolute Different), the search process is done per pixel. To determine the quality of the movement of objects in each frame interpolation is obtained by calculating the PSNR value. PSNR values range from 35 to 40 dB. From the research conducted using the 90 frame interpolation obtained PSNR value decreases.